Определение параметров волны прорыва и оценка возможных последствий затопления - Karpenchuk Игорь; Striganova Марина (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
Destruction of hydro engineering installation of forcing front with formation of break wave stimulates catastrophical flood of locality, causing considerable material damage and founding hazard for population lives. For the purpose of portraying the scheme of break passing, estimation of possible consequences and preparing of bench mark for planning of measure for population protection, it is appropriate to construct a graph of break wave movement.